Guardians of the galaxy : undercover Angle - Caramagna, Joe (Guardians of the galaxy, 2018)
"Titus catches the Guardians when they try to break into the Nova Corps headquarters and agrees to let them go if they infiltrate a notorious group of weapons dealers called the Black Order"--Publisher.